Southeast Kansas Wheat Variety Test Results - 2020 - G. F. Sassenrath; L. Mengarelli; J. Lingenfelser; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2021)
This is a summary of the winter wheat production conditions in southeast Kansas in 2019-2020 and the results of the variety testing. Fifteen hard red and ten soft red winter wheat varieties were compared for yield and test weight. High spring rainfall increased disease pressure; cultivars were rated for Fusarium head blight and stripe rust. Average yield of hard red wheat varieties was above average at 81.1 bu/acre across all varieties. Soft red wheat yield was 102.4 bu/acre across all varieties. For comparison, previous variety yield results are reported from 2016, 2017, and 2018.
Keywords: wheat variety tests; southeast Kansas; hard red winter wheat; soft red winter wheat